Oxidative stress in microbes after exposure to iron nanoparticles: analysis of aldehydes as oxidative damage products of lipids and proteins - Semerád, Jaroslav; Moeder, Monika; Filip, Jan; Pivokonský, Martin; Filipová, Alena; Cajthaml, Tomáš (Environmental science and pollution research international, 2019)
Due to their enhanced reactivity, metal and metal-oxide nanoscale zero-valent iron (nZVI) nanomaterials have been introduced into remediation practice. To ensure that environmental applications of nanomaterials are safe, their possible toxic effects should be described. However, there is still a lack of suitable toxicity tests that address the specific mode of action of nanoparticles, especially for nZVI. This contribution presents a novel approach for monitoring one of the most discussed adverse effects of nanoparticles, i.e., oxidative stress (OS). We optimized and developed an assay based on headspace-SPME-GC-MS analysis that enables the direct determination of volatile oxidative damage products (aldehydes) of lipids and proteins in microbial cultures after exposure to commercial types of nZVI. The method employs PDMS/DVB SPME fibers and pentafluorobenzyl derivatization, and the protocol was successfully tested using representatives of bacteria, fungi, and algae. Six aldehydes, namely, formaldehyde, acrolein, methional, benzaldehyde, glyoxal, and methylglyoxal, were detected in the cultures, and all of them exhibited dose-dependent sigmoidal responses. The presence of methional, which was detected in all cultures except those including an algal strain, documents that nZVI also caused oxidative damage to proteins in addition to lipids. The most sensitive toward nZVI exposure in terms of aldehyde production was the yeast strain Saccharomyces cerevisiae, which had an EC50 value of 0.08 g/L nZVI. To the best of our knowledge, this paper is the first to document the production of aldehydes resulting from lipids and proteins as a result of OS in microorganisms from different kingdoms after exposure to iron nanoparticles.
Keywords: lipidy; testy toxicity; Aldehydes; Bacteria; nanostruktury; Oxidative Stress; železo; Nanostructures; Oxidation-Reduction; Ferric Compounds; Lipids; Iron; železité sloučeniny; oxidace-redukce; oxidační stres; Metal Nanoparticles; kovové nanočástice; Toxicity Tests; aldehydy